2015
DOI: 10.1108/amhid-05-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing psychiatric disorders in people with intellectual disabilities: issues and achievements

Abstract: Purpose – Diagnosing psychiatric disorders (PD) in adults with Intellectual Disability (ID) presents several issues and need specific skills and tools. The purpose of this paper is to provide a detailed description of the current status of art through a systematic mapping of the literature. Design/methodology/approach – The authors reviewed the international literature on the basis of the following questions: what are the issues in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 74 publications
1
21
0
1
Order By: Relevance
“…Potential explanations for this uncertainty include: fundamental differences in diagnostic constructs for people with ID (Bertelli, Rossi, Scuticchio, & Bianco, 2015;; inconsistent definitions of challenging behavior (Hemmings et al, 2013); overlap between the two problems (Holden & Gitlesen, 2009), and practical difficulties in utilising a categorical diagnostic system in both clinical practice and research (Thakker, Bamidele, Ali, & Hassiotis, 2012). Against this challenging backdrop, the research can, at best, be interpreted in different ways (Bernstein, Visconti, Csorba, Radvanyi, & Rojahn, 2015) and, at worst, as contradictory (Hemmings, Deb , Chaplin, Hardy, & Mukherjee, 2013;McCarthy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Potential explanations for this uncertainty include: fundamental differences in diagnostic constructs for people with ID (Bertelli, Rossi, Scuticchio, & Bianco, 2015;; inconsistent definitions of challenging behavior (Hemmings et al, 2013); overlap between the two problems (Holden & Gitlesen, 2009), and practical difficulties in utilising a categorical diagnostic system in both clinical practice and research (Thakker, Bamidele, Ali, & Hassiotis, 2012). Against this challenging backdrop, the research can, at best, be interpreted in different ways (Bernstein, Visconti, Csorba, Radvanyi, & Rojahn, 2015) and, at worst, as contradictory (Hemmings, Deb , Chaplin, Hardy, & Mukherjee, 2013;McCarthy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The need for these attributes is supported by previous research which found that the current lack of knowledge and skills in health assessments for people with an intellectual disability has impinged on the ability of health professionals to provide quality care to this group (Cook & Lennox, ; Lennox, Millar, & Chorlton, ). These skills are also important because of the atypical presentation of mental ill health in some people with an intellectual disability (Bertelli, Rossi, Scuticchio, & Bianco, ; Fuller & Sabatino, ), their complex healthcare needs, and the impact of diagnostic overshadowing on access to quality mental health care (Mason & Scior, ; Michael & Richardson, ; Reiss, Levitan, & Szyszko, ). In particular, the need for mental health professionals to employ an individualized, longitudinal and multisource approach to the assessment process (attribute 11.3) is important because historical literature has shown that the workforce are using symptoms (Lennox & Chaplin, ) rather than a comprehensive longitudinal assessment process, which has been shown to negatively impact on the quality of the assessment provided to people with an intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding as historically there has been contention over the role of mental health professionals in supporting people who present in this manner. This often disputed clinical territory arises out of the belief that behaviours of concern are not a symptom of mental ill health but are part of the person's disability (Bertelli, Rossi, Scuticchio, & Bianco, ). Ensuring that the workforce acquires skills in this area is particularly pertinent because behaviours of concern have been reported as a commonly presenting feature of mental illness for this population (Lennox & Chaplin, ; Torr et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that little or no evidence was generated about seeking consultation or help from nurses or other healthcare professionals, as well as, specialists in the psychiatric field [33]. A more recent review came out with the emerging evidence on using guidelines for the assessment of psychiatric symptoms [34]. These guidelines include a process of identification of psychiatric symptoms, behavioural equivalents, diagnostic criteria, setting, sources of information, screening, and diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%